KEPENTINGAN INDONESIA DALAM MENGGAGAS PERUNDINGAN REGIONAL COMPREHENSIVE ECONOMY PARTNERSHIP - Dedi Parna; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research will explain about the benefit to be achieved by Indonesia in RCEP negotiations initiated within the framework of ASEAN upon its leadership in ASEAN. Negotiations is to discuss the free trade agreements between ASEAN and ASEAN cooperation partners who were previously part of the ASEAN Plus 1trade cooperation. The negotiations initiated because the WTO has failed in formulating multilateral trade rules in the Doha round. This study will also be discussed on how the challenges and opportunities for Indonesia RCEP. This research is a study using research methods literature study. This study uses perspectives and theories of liberalism and the concept of national interest expressed by Jack C. Plano and Olton Roy.The results of this study indicate that Indonesia RCEP initiated in 2011 is to increase trade Indonesia because RCEP high economic potential and Indonesia wants to increase cooperation, especially in the field of small and medium enterprises (SMEs). Opportunities provided by RCEP is the ease in obtaining industrial raw materials more efficiently and quite promising.Keywords: Regional Cooperation Economic Partnership, Cooperation, National Interest